Relation between diarrhea and infection by protozoans in dairy calves - Glombowsky P.* (2017)
© 2017, Springer-Verlag London.Infections caused by protozoa often cause diarrhea in newborn calves, leading to high economic losses to dairy farms, diarrhea, often characterized by malabsorption of nutrients, may lead to malnutrition, weight loss, and high mortality rates. Diarrhea is a common clinical sign found in the first days of a calf life in many dairy and beef cattle farms. Therefore, the aim of our study was to verify if during the first 60 days of live, there was a relationship between the presence of Eimeria, Cryptosporidium, Giardia, and the occurrence of diarrhea in calves, and the association of age and parasite presence. In this study, newborn calves were selected from farms with history of protozoa infections and diarrhea. A total of 26 calves were used in the study, 18 were positives for Giardia spp., 17 for Emeria spp., and 21 for Cryptosporidium spp., considering single and mixed infections. Furthermore, the survival rate of calves due to the presence of diarrhea was significantly different compared to the group without diarrhea, for all three protozoa. In addition, according to this study, it is possible to indicate that the occurrence of diarrhea is highly correlated to the presence of Giardia sp., leading to economic losses due to a low performance and weight gain of infected animals.